PLUNC: a multifunctional surfactant of the airways. (20th July 2011) - Bartlett, Jennifer; Gakhar, Lokesh; Penterman, Jon; Singh, Pradeep; Mallampalli, Rama K.; Porter, Edith; McCray, Paul B.
Abstract : PLUNC (palate, lung and nasal epithelium clone) protein is an abundant secretory product of epithelia throughout the mammalian conducting airways. Despite its homology with the innate immune defence molecules BPI (bactericidal/permeability-increasing protein) and LBP (lipopolysaccharide-binding protein), it has been difficult to define the functions of PLUNC. Based on its marked hydrophobicity and expression pattern, we hypothesized that PLUNC is an airway surfactant. We found that purified recombinant human PLUNC exhibited potent surfactant activity by several different measures, and experiments with airway epithelial cell lines and primary cultures indicate that native PLUNC makes a significant contribution to the overall surface tension in airway epithelial secretions. Interestingly, we also found that physiologically relevant concentrations of PLUNC-inhibited Pseudomonas aeruginosa biofilm formation in vitro without acting directly as a bactericide. This finding suggests that PLUNC protein may inhibit biofilm formation by airway pathogens, perhaps through its dispersant properties. Our data, along with reports from other groups on activity against some airway pathogens, expand on an emerging picture of PLUNC as a multifunctional protein, which plays a novel role in airway defences at the air/liquid interface.